Age Is Just a Number: Adults Deserve the Same Access to Genetic Testing as Children. Issue 1 (January 2020) - Perry, M. Scott
Clinical utility of multigene panel testing in adults with epilepsy and intellectual disability Borlot F, De Almeida BI, Combe SL, Andrade DM, Filloux FM, Myers KA. Epilepsia . 2019;60(8):1661-1669. doi:10.1111/epi.16273. Objective: To determine the diagnostic yield of a commercial epilepsy gene panel in adults with chronic epilepsy and accompanying intellectual disability, given that genetic evaluation is often overlooked in this group of patients. Methods: This is a cross-sectional study analyzing the results of epilepsy gene panels including up to 185 genes in adult epilepsy patients with intellectual disability, according to Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition . Patients with acquired structural brain abnormalities or known chromosomal abnormalities were excluded. Results: From approximately 600 patients seen from January 2017 to June 2018 at a single academic epilepsy center, 64 probands and 2 affected relatives (32 males, mean age = 31 years ± 10) were selected and clinically tested. Fourteen probands (14/64 = 22%; 4 males, mean age = 32 years ± 10) were found to have pathogenic or likely pathogenic variants in the following genes: SCN1A, GABRB3, UBE3A, KANSL1, SLC2A1, KCNQ2, SLC6A1, HNRNPU, STX1B, SCN2A, PURA, and CHD2 . Six variants arose de novo, and the inheritance was not determined in 8. Nine probands (64%) had severe or profound intellectual disability, and 5 (35%) had autistic features. Eight patients (57%) had a diagnostic change from presumptive clinical diagnosis prior to genetic testing. Significance: We were able to demonstrate that a commercial epilepsy gene panel can be an important resource in clinical practice, identifying the etiology in 22% of adults with epilepsy and intellectual disability. The diagnostic yield is similar to previously reported pediatric cohorts. Larger samples would be required to evaluate the more prevalent genotypes among patients with adult epilepsy.